Improving Qur'an Reading Skills through the Implementation of the Iqra' Method - Dewi Sholeha; Annisa Annisa; Sandhika Anggun Awaliyani (Indonesian Publication Center, 2024)
The lack of ability to read the Qur'an that occurs at this time is influenced by several factors, such as: some children who do not yet know the hijaiyyah letters and cannot distinguish one letter from another, children cannot read and pronounce the Qur'an fluently according to makhraj, children cannot distinguish correctly the sound of single letters that have adjacent makhraj, children cannot distinguish between short and long readings, children do not yet know the reading of kasrah, dhamah, and fathah readings, and teachers do not use learning methods when learning the Qur'an. Therefore, it is necessary to apply the right learning method to improve children's ability to read the Qur'an. One of these methods is the iqra' method. Referring to this statement, the researcher is interested in conducting a literature study to identify efforts to improve the ability to read the Qur'an through the application of the iqra' method. The results of this study indicate that the Iqro' method is considered one of the fast methods that can improve the ability to read the Qur'an to students directly without spelling it out, the learning system uses CBSA (Active Student Learning Method), practical and varied guidebooks, and the teachers who teach are also professional because they are required to have a shahadah.